2019
DOI: 10.1037/dev0000817
|View full text |Cite
|
Sign up to set email alerts
|

Do school-related experiences impact personality? Selection and socialization effects of impulse control.

Abstract: Personality traits are well-known predictors of academic success across all levels of education. However, whether school provides an environment to cultivate and promote personality traits is largely unknown. Theories about personality development give reasons to assume that enduring experiences at school could lead to prolonged personality changes. We therefore studied the dynamic interplay of impulse control-an important predictor for educational and life outcomes-and perceptions of school-related experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 84 publications
2
37
0
Order By: Relevance
“…Sensation-seeking was also measured using a 3-item question set from previous research (Bollich et al, 2020;Brandt et al, 2019;Harden & Tucker-Drob, 2011). Similar to impulsivity, these questions were answered by participants 10 years and older.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensation-seeking was also measured using a 3-item question set from previous research (Bollich et al, 2020;Brandt et al, 2019;Harden & Tucker-Drob, 2011). Similar to impulsivity, these questions were answered by participants 10 years and older.…”
Section: Methodsmentioning
confidence: 99%
“…Past research has found the development of impulse control is positively related to some academic-related factors such as school satisfaction and teacher support (Brandt et al, 2019).…”
Section: Which Traits Change the Most And Least Due To Substance Use?mentioning
confidence: 99%
“…Personality. For Impulsivity and Sensation Seeking, we used the same 3-item question sets used in previous research (Brandt, Mike, & Jackson, 2019;Harden & Tucker-Drob, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that peers can be detrimental for the development of impulsivity. However, positive peer experiences, are associated with positive changes in impulse control (Brandt, Mike & Jackson, 2019), suggesting that peers do not only have negative effects on the development of impulsivity.…”
Section: Socialization Effects Of Incarcerationmentioning
confidence: 99%
“…Our findings attempt to accurately match the first experience of FV and personality measurement for understanding the relationships between them. It may help us to understand the personality development caused by life events (Brandt, Mike, & Jackson, 2019). After learning which life events may bring personality changes, we can further study the characteristics of these events and the mechanisms of changes (Wrzus & Neyer, 2016).…”
Section: Discussionmentioning
confidence: 99%